2013
DOI: 10.1136/neurintsurg-2013-010820
|View full text |Cite
|
Sign up to set email alerts
|

Silent embolism after stent-assisted coiling of cerebral aneurysms: diffusion-weighted MRI study of 75 cases

Abstract: Thromboembolic events are common after stent-assisted coiling with an incidence comparable to DWI studies after coiling alone. Despite several devices and low operator experience, stent-assisted coiling for intracranial aneurysms has a very low risk of permanent neurologic disability. Further studies are necessary to improve the safety of stent-assisted coiling for patients in conditions with increased risk potential (age, procedure time, stent length).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 26 publications
2
43
3
1
Order By: Relevance
“…In a series of 34 consecutive patients undergoing elective coiling for unruptured aneurysms, Matsushige et al 20 reported that 76% of patients had high-signal spots on DWI. Hahnemann et al 21 found that nearly two-thirds of patients undergoing stent-assisted coiling had postprocedural ischemic lesions on DWI in a series of 75 patients. Our study is considerably smaller, and further studies reporting the incidence of DWI changes following PED placement are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 34 consecutive patients undergoing elective coiling for unruptured aneurysms, Matsushige et al 20 reported that 76% of patients had high-signal spots on DWI. Hahnemann et al 21 found that nearly two-thirds of patients undergoing stent-assisted coiling had postprocedural ischemic lesions on DWI in a series of 75 patients. Our study is considerably smaller, and further studies reporting the incidence of DWI changes following PED placement are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…2-4, 8,9,15,22,[24][25][26] One possible reason for the lower rate in our study may have been the strict anticoagulation and antiplatelet regimen that was used. Our patients received premedication with 2 antiplatelet drugs for > 5 days (preferably ~ 10 days) prior to their procedure, regardless of whether the use of a stent was anticipated.…”
Section: 23mentioning
confidence: 99%
“…If we did not include other variables such as the assistive techniques, the result could have differed, as was suggested by another report. 9 The use of antithrombotics such as antiplatelet and anticoagulant drugs is obviously a very important issue. Heparin use has previously been suggested as an important variable.…”
Section: 23mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] To reduce thromboembolic complications, many studies investigated the association between thromboembolism and aneurysm and/or patient factors. [5][6][7][8] Previous studies have demonstrated that 30%-60% of endovascular coil embolizations for unruptured aneurysms show ischemic lesions on postprocedural diffusion-weighted images. Although most of the lesions seem to be benign, some could result in permanent neurologic sequelae.…”
mentioning
confidence: 99%